Pengendalian Kekerasan Seksual Terhadap Anak di Kabupaten Karawang - Azizi, Fakhri; Noor, Aslan (Peneliti.net, 2024)
Crime is a name or label given by people to assess certain actions, as evil, all forms of treatment that disturb and damage their basic rights in various forms of inhumane use and exploitation which must be stopped immediately without exception. How to control sexual violence against children Legal Protection for Children from Sexual Violence as a Form of Fulfilling Children's Rights in Karawang Regency? Women's Empowerment and Child Protection Service. The data collection procedure in writing this research was by means of literature and field studies. Data analysis uses qualitative analysis. Based on the results of research and discussion, what factors cause criminal acts of sexual violence against children?Social deviance factors, lack of supervision from parents, sexual disorders. How to achieve goals in controlling child sexual violence in Karawang Regency? The consequences of children dealing with the law for criminal acts of sexual violence by perpetrators include legal consequences such as legal protection and rehabilitation, sexual trauma, feeling helpless, how to control sexual violence against children as victims and the responsibility of the government, parents, In child protection, society is in conflict with the law for victims of criminal acts of sexual violence. The government's responsibility in child protection is to provide rehabilitation efforts both within and outside the institution